Friendship and rivalry between neighbours. Cultural tourism on the border of Ourense and Portugal - Mesía López, Ana (2022)
The proposed physical space, in this work, is the border between Spain and Portugal, in the province of Ourense, where war events occurred that provided the landscape with a network of castles for control and surveillance; an architecture that articulated the territory and that reached our days in various states of conservation. In this context, the valorization of defensive heritage to design a cultural route linked to the history of the border begins with a bibliographic study to have the state of the art and subsequent field work to visit and analyze the tourist possibilities of these properties. Also, it is necessary to review the hotel infrastructure, since the objective is to seek a comprehensive tourist experience. Consequently, the itinerary should contribute to the revitalization of the rural world, the knowledge of border history and the presentation of new job opportunities.